2013
DOI: 10.1890/12-1313.1
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry predicts habitat selection by an avian herbivore at multiple spatial scales

Abstract: Abstract. Animal habitat selection is a process that functions at multiple, hierarchically structured spatial scales. Thus multi-scale analyses should be the basis for inferences about factors driving the habitat selection process. Vertebrate herbivores forage selectively on the basis of phytochemistry, but few studies have investigated the influence of selective foraging (i.e., fine-scale habitat selection) on habitat selection at larger scales. We tested the hypothesis that phytochemistry is integral to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 25 publications
(34 reference statements)
3
93
0
Order By: Relevance
“…Sage-grouse tended to occupy plots in landscapes dominated (50-70% landcover) by a mixture of dwarf sagebrush landcover and big sagebrush steppe landcover. This finding is congruent with our plot-level findings and other studies that have shown selection for this type of habitat (Erickson et al 2009, Atamian et al 2010, Frye et al 2013. Availability of even a small amount of riparian landcover (0.2-2.8% landcover within 5 km) increased the probability of sage-grouse occupancy, but occupancy was still likely in landscapes without this habitat element if other conditions were favorable.…”
Section: Plot-and Landscape-scale Predictors Of Sage-grouse Occupancysupporting
confidence: 92%
See 2 more Smart Citations
“…Sage-grouse tended to occupy plots in landscapes dominated (50-70% landcover) by a mixture of dwarf sagebrush landcover and big sagebrush steppe landcover. This finding is congruent with our plot-level findings and other studies that have shown selection for this type of habitat (Erickson et al 2009, Atamian et al 2010, Frye et al 2013. Availability of even a small amount of riparian landcover (0.2-2.8% landcover within 5 km) increased the probability of sage-grouse occupancy, but occupancy was still likely in landscapes without this habitat element if other conditions were favorable.…”
Section: Plot-and Landscape-scale Predictors Of Sage-grouse Occupancysupporting
confidence: 92%
“…First, contemporary studies spanning four western states and multiple seasons of sage-grouse habitat use have found that sage-grouse use dwarf sagebrush habitats disproportionately to their availability or more frequently than big sagebrush sites (Erickson et al 2009, Atamian et al 2010, Bruce et al 2011, Hagen et al 2011, Frye et al 2013. This is likely because the leaves of dwarf sagebrush species have significantly lower monoterpene concentrations than those of Wyoming sagebrush (Frye et al 2013). Monoterpenes are plant secondary metabolites that have deleterious effects on herbivores.…”
Section: Plot-scale Predictors Of Sage-grouse Occupancymentioning
confidence: 99%
See 1 more Smart Citation
“…Brushtail possums (Trichosurus vulpecula), swamp wallabies (Wallabia bicolor) (Bedoya-Perez et al 2014) and African bushbabies (Otolemur crassicaudatus) (McArthur et al 2012) all demonstrate earlier patch quitting, quantified as higher Giving-Up-Density (GUD) at food patches with increasing toxin concentration. Similarly, free-ranging koalas (Phascolarctos cinereus), pygmy rabbits (Brachylagus idahoensis) and the avian herbivore, the greater sage-grouse (Centrocercus urophasianus) select plants or plant patches with low toxin concentration (Moore and Foley 2005;Frye et al 2013;Ulappa et al in press).…”
Section: Dealing With Plant Chemistrymentioning
confidence: 99%
“…Another reason is that researchers tend to regard nutrients as "therapeutic" components that always result in positive consequences whereas PSMs are considered "toxic" components with inevitable negative repercussions. As such, PSMs (Cruz-Rivera and Hay, 2003;Duffy and Paul, 1992;Felton et al, 2009;Van Alstyne et al, 2009), in others, PSMs are more important (Dearing et al, 2000;Erhard et al, 2007), and in still other cases, these factors are equally important or act synergistically to influence foraging behavior (Duffy and Paul, 1992;Frye et al in press, Simpson and Raubenheimer, 2001). While approaches, such as the geometric framework, have helped researchers study how herbivores regulate nutrient needs in variable nutritional and PSM environments (Behmer, 2009), what remains poorly understood is why certain species respond to specific thresholds of PSMs or nutrients and others do not.…”
Section: Introductionmentioning
confidence: 99%